Analisis Manhaj Ilmu Rasm dalam Surah Al-Baqarah: Kajian Manuskrip Al-Quran MSS 4322 Karangan Pangeran Jimat: Analysis of Manhaj Rasm in Surah Al-Baqarah: A Study of Manuscripts Al-Quran MSS 4322 by Pangeran Jimat - Che Omar, Siti Azwanie; Ariffin, Sedek (Jurnal Usuluddin, 2022)
Rasm is a learn about the writing of the mushaf al-Quran specifically either in writing, pronunciation or the forms of letters used. The purpose is as a guide to the next copyist of the Qur'an so that his writing does not deviate from the writings of the companions of the Prophet SAW. The main focus of this study is to analyze the manhaj rasm found in surah al-Baqarah from the manuscript al-Quran MSS 4322 collection of the National Library of Malaysia. Manuscript al-Quran MSS 4322 is a handwritten by Pangeran Jimat in Madura, Indonesia. Pangeran Jimat was a sultan who ruled Madura in the 17th century AD. This study was conducted through a philological approach. The method used throughout this study is the method of data collection through documentation method that is by analyzing the text of the Qur'an MSS 4322. The findings show that the analysis of official knowledge in the manuscript of the Qur'an MSS 4322 clearly shows the writing of official knowledge of the manuscript al-Quran MSS 4322 does not take the main view, Abu Dawud Sulayman al-Najah as the opinion in the mushaf of Madinah and the second view of Abu Amr Uthman bin Sa'id al-Dani represents the view of the mushaf of the Libyan Jamahiriyah. Especially, in setting seven methods in Uthman official writing, namely hadhf alif, ziyadah alif, ziyadah waw, ziyadah ya and words that contain two or more readings. All in all, more to the writing of the Imla’i rasm except only on the determination of the method of hadhf alif on ha tanbih, hadhf alif on the noun isim, ibdal alif on waw, wasl, fasl and the use of hamzah wasal and hamzah qata ’only using the Ottoman rasm. The findings of this study, the author proposes that this study can be done continuously on other surah in the manuscript of the Qur'an MSS 4322, especially aspect rasm. Therefore, this manuscript of the Qur'an is a great manuscript that will enhance the dignity and writings of previous scholars academically and more authoritatively to the digital generation, especially in the field of the Qur'an.